VALUASI EKONOMI EKOSISTEM HUTAN MANGROVE DI NEGERI PASSO KOTA AMBON - Willem Talakua (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Extensive mangrove forest in coastal area of Ambon city reached 64,316 acres, with shoreline length is 8,951 m based on mangrove forest, that the existing is spread in 13 villages, one of them is Passo village that has mangrove area 27.8761 acres. The existing of mangrove forest in Passo or in the other area in Ambon city not only gives physical benefit and economy but also biological benefit, but often misused  by  the  local  community  is  by  doing  over  exploitation  that  can  destruct  the mangrove ecosystem.  This  case  is  caused  by  the  low  awareness  the  local  community  about  how  important mangrove forest and also the lowness of appreciation of mangrove forest potentials as economic asset. The research is aimed to analyze the economic value of the mangrove forest in coastal area of Passo village, Ambon city. Data collection is done by observation, interview and also from secondary data. Data  analyzing  data  based  on  natural  resources  concept  or  environment  concept  according  to Suparmoko  (2002),  and  Reuitenbeek  (1991).  Research  result  shows  the  extensive  of  Passo’s mangrove  forest  is  27,8761  acres,  and  produces  total  economic  value  of  185.800.570  rupiah/year consist of direct benefit value 11.449.423 rupiah/year, indirect benefit value 160.379.819 rupiah/year, existing benefit 9.804.125 rupiah/year, and choice benefit 4.167.203 rupiah/year. Keywords : economic valuation, mangrove forest ecosystem, Passo village.